Increasing of “Keprok” Citrus Production in the Andisols of Karo by a Local Compound Fertilizers - Enggis Tuherkih; . Sukristiyonubowo (JOURNAL OF TROPICAL SOILS, 2010)
Increasing of “Keprok” Citrus Production in the Andisols of Karo by a Local Compound Fertilizers (E Tuherkih and Sukristiyonubowo): The improvement of “keprok” citrus production in term of quantity and quality depends on soil properties and fertilization.  Many factors affected efectiveness and efficiency of fertilizers i.e. soil, climate, plant species, growth period of plant, plant productivity, and type and rate of fertilizers. Study on the effect of SUMUT-1 and SUMUT-2 compound fertilizers on keprok citrus production was carried out in Sukadame Village, Tanah Karo District from January to December 2008. The purpose of the research were to evaluate the effectiveness of new compound fertilizer SUMUT-1 and SUMUT-2 on leaf nutrient content, quality and quantity production of “keprok” citrus as well as to determine the optimum rate of SUMUT-1 dan SUMUT-2. Ten treatments were tested and arranged into a randomized completely block design with three replications. The fertilizer application rates of SUMUT 1 and SUMUT 2 were 400, 550, 700, dan 850 kg-1ha-1year-1, meanwhile dosages of fertilizer recomended application of NPK originated from single fertiliser namely urea, SP-36, and KCl and farmer practice were used as control.  The results indicated that application of SUMUT-1 and SUMUT-2 were more effective than fertilizers coming from single NPK fertilizer with RAE value >100%. Furthermore, SUMUT-1 was better than SUMUT-2 in improving N, P, K contents in citrus leaf. The optimum application rate of SUMUT-1 was 700 kg-1ha-1year-1 reaching the citrus production of 36,29 Mg-1  ha-1  year-1 with fruit grade of about  51% AB and 49% CD. These matched with the SPO (Standard Procedure Operation) for citrus of about 20 Mg-1 ha-1 year-1.